Evaluating impacts of CO2 and CH4 gas intrusion into an unconsolidated aquifer: fate of As and Cd - Lawter, Amanda; Qafoku, Nikolla P.; Shao, Hongbo; Bacon, Diana; Brown, Christopher (Frontiers in Environmental Science, 2015)
The sequestration of carbon dioxide (CO2) in deep underground reservoirs has been identified as an important strategy to decrease atmospheric CO2 levels and mitigate global warming, but potential risks on overlying aquifers currently lack a complete evaluation. In addition to CO2, other gases such as methane (CH4) may be present in storage reservoirs. This paper explores for the first time the combined effect of leaking CO2 and CH4 gasses on the fate of major, minor and trace elements in an aquifer overlying a potential sequestration site. Emphasis is placed on the fate of arsenic (As) and cadmium (Cd) released from the sediments or present as soluble constituents in the leaking brine. Results from macroscopic batch and column experiments show that the presence of CH4 (at a concentration of 1 % in the mixture CO2/CH4) does not have a significant effect on solution pH or the concentrations of most major elements (such as Ca, Ba, and Mg). However, the concentrations of Mn, Mo, Si and Na are inconsistently affected by the presence of CH4 (i.e., in at least one sediment tested in this study). Cd is not released from the sediments and spiked Cd is mostly removed from the aqueous phase most likely via adsorption. The fate of sediment associated As [mainly sorbed arsenite or As(III) in minerals] and spiked As [i.e., As5+] is complex. Possible mechanisms that control the As behavior in this system are discussed in this paper. Results are significant for CO2 sequestration risk evaluation and site selection and demonstrate the importance of evaluating reservoir brine and gas stream composition during site selection to ensure the safest site is being chosen.